Eligibility and selection criteria under the Open Registration System (ORS) for low cost houses in Malaysia - Abdul Rashid, Khairuddin; Ibrahim, Mansor; Mohit, Mohammad Abdul; Shuid, Syafiee (2005)
Computerized Open Registration System (ORS) for low cost house buyers was introduced by the Malaysian Ministry of Housing and Local Government (MHLG) in May 1997. The ORS aims to standardize the policies and selection criteria for the purchase of low cost houses developed by the Malaysian public and private sectors. In addition, the ORS functions as a database containing information on persons that are considered eligible to purchase low cost houses. The paper highlights the modus operandi and key issues pertaining to the implementation of the current ORS in Malaysia.